Examining Several Strategies for the Chemical Synthesis of Phosphorylated Histone H3 Reveals the Effectiveness of the Convergent Approach. Issue 21 (3rd April 2019) - Jbara, Muhammad; Maity, Suman Kumar; Brik, Ashraf
Abstract : Phosphorylation of Ser57 of the histone H3 was suggested to interact with the acetylated Lys56 of histone H3 and possibly affect DNA replication. Yet the exact role of Ser57 remains unknown due to difficulties in obtaining phosphorylated H3 at Ser57. Herein, we present the challenges and the solutions in the first total chemical synthesis of phosphorylated and unphosphorylated histone H3 analogues utilizing hydrazide‐based native chemical ligation approach coupled with palladium‐mediated thiazolidine decaging chemistry to provide each one of these analogues in highly efficient manner. We envision this synthesis would set the ground to elucidating the role of the phosphorylation and its cross‐talk with acetylation mark in H3 in the DNA damage response. Abstract : Herein presented the challenges and the solutions in the chemical synthesis of phosphorylated and unphosphorylated histone H3 analogues utilizing hydrazide‐based native chemical ligation approach coupled with palladium‐mediated thiazolidine decaging chemistry. This synthesis sets the stage to elucidate the role of phosphorylated Ser57 in chromatin context.